CHEMISTRY ENGLISH PROGRAM AT RAMAPATI RADIO STATION FOR THE STUDENTS SPEAKING SKILL IMPROVEMENT - Ninik Suryatiningsih (Universitas Muhammadiyah Ponorogo, 2015)
Speaking is an important skill in learning a language. By speaking, students can express their ideas through words and sentences. To increase the speaking skill, the students need to practice to speak English. There are many activities that can be done to practice speaking. One of it, is by join and listen to CHEMISTRY Radio English Program in Ramapati Pasuruan 93 FM.In this research, the researcher used descriptive study as the research design and used documentation and questionnaire as the research instrument. The researcher chose English department students on the second semester of STKIP PGRI Pasuruan. The researcher was interested in finding out the students interest in CHEMISTRY Radio English Program. The researcher described the students frequency of participation in this program, the reasons in listening and joins this program, the benefits they get when they join this program and the problems that the students face when they participate in this program.Finally, the students of English Department of STKIP PGRI Pasuruan, especially 2013 generation got so many advantages by listening and joining CHEMISTRY Radio English Program. By joining this program, they got more score from their lecturer and increased their ability in speaking English.